Protein Kinase A Effects of an Expressed PRKAR1A Mutation Associated with Aggressive Tumors - Meoli, Elise (2008)
Most PRKAR1A tumorigenic mutations lead to nonsense mRNA that is decayed; tumor formation has been associated with an increase in type II protein kinase A (PKA) subunits. The IVS6+1G>T PRKAR1A mutation leads to a protein lacking exon 6 sequences [R1αΔ184-236 (R1αΔ6)]. We compared in vitro R1αΔ6 with wild-type (wt) R1α. We assessed PKA activity and subunit expression, phosphorylation of target molecules, and properties of wt-R1α and mutant (mt) R1α; we observed by confocal microscopy R1α tagged with green fluorescent protein and its interactions with Cerulean-tagged catalytic subunit (Cα). Introduction of the R1αΔ6 led to aberrant cellular morphology and higher PKA activity but no increase in type II PKA subunits. There was diffuse, cytoplasmic localization of R1α protein in wt-R1α– and R1αΔ6-transfected cells but the former also exhibited discrete aggregates of R1α that bound Cα; these were absent in R1αΔ6-transfected cells and did not bind Cα at baseline or in response to cyclic AMP. Other changes induced by R1αΔ6 included decreased nuclear Cα. We conclude that R1αΔ6 leads to increased PKA activity through the mt-R1α decreased binding to Cα and does not involve changes in other PKA subunits, suggesting that a switch to type II PKA activity is not necessary for increased kinase activity or tumorigenesis.